2009
DOI: 10.1243/14680874jer04409
|View full text |Cite
|
Sign up to set email alerts
|

Effect of injection timing on gasoline homogeneous charge compression ignition particulate emissions

Abstract: Particulate emissions from homogeneous charge compression ignition (HCCI) engines are often considered as negligible and the measurement of particulate matter (PM) with HCCI combustion systems has been rare. An earlier publication in the literature and the authors' own recently published work suggest that PM emissions from gasoline direct injection (DI) HCCI engines should not be neglected. It has been shown that PM emissions from HCCI engines, although generally lower, can be similar to spark ignition (SI) le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 22 publications
1
9
0
Order By: Relevance
“…It is reported for a hydrogen (SI) engine that with increasing in-cylinder temperature, organic carbon levels of the PM also increase [36]. This density was also used for PM studies on a gasoline fueled HCCI engine [28]. Similar phenomenon may also be taking place in HCCI combustion engines, and upon increasing the intake air temperature, the rate of pressure rise increases rapidly.…”
Section: F Ig 7 V a R Ia Tio N O F T O Ta L N U M B E R C O N C E Nmentioning
confidence: 99%
See 1 more Smart Citation
“…It is reported for a hydrogen (SI) engine that with increasing in-cylinder temperature, organic carbon levels of the PM also increase [36]. This density was also used for PM studies on a gasoline fueled HCCI engine [28]. Similar phenomenon may also be taking place in HCCI combustion engines, and upon increasing the intake air temperature, the rate of pressure rise increases rapidly.…”
Section: F Ig 7 V a R Ia Tio N O F T O Ta L N U M B E R C O N C E Nmentioning
confidence: 99%
“…Findings of numerous medical investigations indicate that several health effects are associated with ultrafine particles having diameters below 100 nm, which are typically emitted during the combustion of fossil fuels. Parameters such as the air/fuel ratio, fuel injection timing, and engine load can increase PM emissions by as much as three orders of magnitude as compared to those for a stoichiometric operation in gasoline engines [20][21][22], In HCCI engine, PM or smoke emissions are frequently reported as "near zero" or "ultralow" [24], However, recent stud ies revealed that although the total PM mass is indeed low, signifi cant numbers of these particles remain in the size range below lOOnm mobility diameter [25][26][27][28][29][30], The study conducted for inves tigation of port fuel injection timing on methanol fueled HCCI combustion showed that particle number emissions are dependent on fuel injection timings and found that start of injection during closed intake valve condition have lower peak concentration of particles [7]. Therefore, measurement and control of engine PM emissions is absolutely necessary.…”
Section: Introductionmentioning
confidence: 99%
“…Misztal et al conducted more detailed study of HCCI particle size distributions using DI-HCCI system by injecting unleaded gasoline directly into the cylinder employing negative valve overlap (NVO) to capture residuals [26]. Other investigation by Misztal et al examined the role of injection timing in PM formation in the same engine [27]. The DI mode of fuel delivery led to discovery of high sensitivity of PM formation to injection timings.…”
Section: Introductionmentioning
confidence: 99%
“…With HCCI combustion, emissions of PM, or smoke, are frequently described as "near zero" or "ultra-low" [12]. However recent investigations have shown that although the total mass of PM is indeed low, significant numbers of particles remain in the size ranges below 100 nm mobility diameter [13][14][15][16][17]. This size range is well within the measurement capabilities of modern nano-particle instrumentation, which is well suited for studies in HCCI particle emissions.…”
Section: Introductionmentioning
confidence: 99%
“…Misztal et al conducted more detailed study of HCCI particle size distributions using DI-HCCI system by injecting unleaded gasoline directly into the cylinder employing negative valve overlap (NVO) to capture residuals [15]. Other investigation by Misztal et al examined the role of injection timing in PM formation in the same engine [16]. The DI mode of fuel delivery led to discovery of high sensitivity of PM formation to injection timings.…”
Section: Introductionmentioning
confidence: 99%